Yeast Probiotics Shape the Gut Microbiome and Improve the Health of Early-Weaned Piglets - Xu, Jinqiang; Li, Yuhui; Yang, Zhiqiang; Li, Chunhui; Liang, Hongyan; Wu, Zuowei; Pu, Wanxia (Frontiers in Microbiology, 2018)
Weaning is one of the most stressful challenges in the pig’s life, which contributes to dysfunctions of intestinal and immune system, disrupts the gut microbial ecosystem, and therefore compromises the growth performance and health of piglets. To mitigate the negative impact of the stress on early-weaned piglets, effective measures are needed to promote gut health. Toward this end, we tamed a Saccharomyces cerevisiae strain and developed a probiotic Duan-Nai-An, which is a yeast culture of the tamed Saccharomyces cerevisiae on egg white. In this study, we tested the performance of Duan-Nai-An on growth and health of early-weaned piglets and analyzed its impact on fecal microbiota. The results showed that Duan-Nai-An significantly improved weight gain and feed intake, and reduced diarrhea and death of early-weaned piglets. Analysis of the gut microbiota showed that the bacterial community was shaped by Duan-Nai-An and maintained as a relatively stable structure, represented by a higher core OTU number and lower unweighted UniFrac distances across the early weaned period. However, fungal community was not significantly shaped by the yeast probiotics. Notably, 13 bacterial genera were found to be associated with Duan-Nai-An feeding, including Enterococcus, Succinivibrio, Ruminococcus, Sharpea, Desulfovibrio, RFN20, Sphaerochaeta, Peptococcus, Anaeroplasma, and 4 other undefined genera. These findings suggest that Duan-Nai-An has the potential to be used as a feed supplement in swine production.